2010
DOI: 10.1002/sia.3333
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of polyethylene glycols onto nanometer silica surface by 1,4‐phenylene diisocyanate

Abstract: In this paper, polyethylene glycol (PEG) molecules have been grafted onto the surface of nanometer silica in toluene by using 1,4-phenylene diisocyanate (PPDI) as a coupling agent, and dibutyltion dilaurate (DBTDL) as a catalyst. This process was executed by using a one-step procedure involving a first reaction of PPDI with silica and a subsequent reaction of isocyanate-bound silica with PEG. The PEG-grafted silica has been characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…These kinds of hydroxyl groups could be substituted by multifunctional active agents such as amino silane, scandium triflate, and organic isocyanate. After surface modification of nanosilica, the remained functional groups are active sites for subsequent polymer grafting 15, 19, 21, 22. Also, toluene 2,4‐di‐iso‐cyanate (TDI) posses high reactivity with hydroxyls because of its highly unsaturated bonds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These kinds of hydroxyl groups could be substituted by multifunctional active agents such as amino silane, scandium triflate, and organic isocyanate. After surface modification of nanosilica, the remained functional groups are active sites for subsequent polymer grafting 15, 19, 21, 22. Also, toluene 2,4‐di‐iso‐cyanate (TDI) posses high reactivity with hydroxyls because of its highly unsaturated bonds.…”
Section: Introductionmentioning
confidence: 99%
“…TDI has two isocyanate groups with different activities at para and ortho positions. Recently, several papers reported the utilization of TDI as a surface modifier of silica for subsequent grafting 17, 18, 20–23…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the thermal degradation behavior of the obtained materials, it was observed that their degradation profile changes with the number of the organic layers grafted onto the silica surface. Pure silica had a slight weight loss at 300°C, the loss caused by the hydroxyl group according to the literature [25]. Since the inorganic part (silica) of the composite materials lost almost none of its weight during the heating period, all of the weight loss of the studied materials should only come from the degradation of the organic part.…”
Section: Resultsmentioning
confidence: 67%
“…Surface functionalization is an efficient techniques for improving the surface performance of existing polymers without great changes to their bulk properties. Various hemocompatible moieties have been used for surface modification; these have included poly(ethylene glycol) (PEG) and its derivatives, poly(vinyl pyrrolidone), zwitterionic materials, heparin, chitosan, proteins, and lysine . Furthermore, bulk modification is another method for obtaining biocompatible surfaces.…”
Section: Introductionmentioning
confidence: 99%